Rancang Bangun Sistem Sortir Telur Ayam - Irfan Fauzi Aristianto; Mohammad Ramdhani; IG. Prasetya Dwi Wibawa (eProceedings of Engineering, 2020)
Abstract Based on Indonesian National Standards SNI No. 33926: 2008, Egg weight is divided into 3 groups, namely small less than 50 g, medium 50 g to 60 g and greater than 60 g. With these criteria, the grouping is done manually so that the results of egg grouping are not uniform because it depends on the subjects who do the sorting and the time used is relatively longer. The use of grading machines is a solution to overcome the problem. This research consisted of the design phase, the manufacturing stage and the performance test stage for the egg grading system. The design begins by determining the criteria and system specifications. The chicken egg sorting system uses a load cell sensor to identify egg weight and drive the servo motor. The egg grading machine can work with an accuracy of a load cell of 98.28% and a 100% rectifier accuracy is successful. So that the eggs can be sorted according to weight criteria which are divided into 3 groups, namely small, medium and large. Keywords : Telur, mesin grading, load cell